1981
DOI: 10.2307/414380
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Language Learning and Teaching

Abstract: No pan of this publication may be reproduced. stored in a retrieval system, or transmitted m any form or by any means, electronic, mechanical, photocopying, recording, or otherwise. without the prior peimi>sion of the publisher Pearson Education. 10 Bank Street. White Plains, MY 10606 Staff credits: The people who made up the Principles of Language Learning and Teaching, Fifth Edition team, representing editorial, production, design, ;ind manufacturing, are Danielle Belfiore. TraCev Munz Cataldo. Dave Dickev, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
155
0
16

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(176 citation statements)
references
References 46 publications
5
155
0
16
Order By: Relevance
“…Another result showed that intralingual transfer or errors because of the language itself are significantly dominant compared to the interlingual transfer. This is in line with Terrell & Brown (1981) statement that the effect of intralingual transfer to create errors overshadow other factors. However, research by (Puspita, 2019) showed that errors performed by English learners.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Another result showed that intralingual transfer or errors because of the language itself are significantly dominant compared to the interlingual transfer. This is in line with Terrell & Brown (1981) statement that the effect of intralingual transfer to create errors overshadow other factors. However, research by (Puspita, 2019) showed that errors performed by English learners.…”
Section: Introductionsupporting
confidence: 90%
“…According to Terrell & Brown (1981), errors made by language learners come from several sources; they are interlingual transfer, intralingual transfer, the context of learning, and communicative strategy. Out of all sources, intralingual transfer (errors within the language) is the main factor in learning a language.…”
Section: Introductionmentioning
confidence: 99%
“…In order to know their ability in completing those processes well, their writing should be analyzed by using certian criterias. One of the idea was as proposed by (Terrell & Brown, 2006) who mentioned that there were five criterias in analyzing writing: content, organization, grammar, vocabulary and mechanic.…”
Section: Writingmentioning
confidence: 99%
“…In analyzing questionnaire, the writer analyze the percentage of each criteria. On the other hand, in analyzing the writing tests, the writer used writing scoring rubric which was adopted from (Terrell & Brown, 2006) which consisted of five criterias: content, organization, grammar, vocabulary, and mechanic.…”
Section: Data Analysis Techniquementioning
confidence: 99%
“…Meanwhile, productive skills include speaking and writing. (Terrell & Brown, 2006), English teaching and learning process not only integrates the learners' skill to use those four macro skills, but also deals with other sub skills, such as grammatical rules, vocabulary, and the likes. Moreover, Brown concludes that the difference in level of competency tend to make this heterogeneity a drawback to acquire a foreign language (Brown, 2000).…”
Section: Literature Review English Teaching and Learning Principlesmentioning
confidence: 99%